(untitled) (EAAE Annual Conference Proceedings, 2025)
Demolishing existing buildings poses significant environmental, economic, and socio-cultural challenges worldwide. In Germany, reforms to the building code in the 1990s replaced the requirement for a demolition permit with a simple notification procedure. This shift has made it easier to demolish non-protected buildings, conflicting with the European Green Deal’s goals for resource conservation and climate protection. While the preservation and continued use of existing buildings make a significant contribution to the conservation of grey energy, architects still have only marginal influence on demolition decisions, as these are often made before they are commissioned by building owners and investors. Against this backdrop, questions arise as to who the key players are in demolition decisions, how architects are currently contributing to reducing or avoiding demolition, and what tools are available to them to influence these decisions. This study examines these dynamics through a research-oriented elective module at the School of Architecture Bremen (SoAB), led by the Chair of Sustainable Planning and Building in Urban Contexts. Advanced Bachelor’s and Master’s students participated in the module, analyzing real-world projects at risk of demolition. Employing methods such as media research, stakeholder mapping, and SWOT analysis, students investigated the motivations, communication strategies, and key actors involved in demolition processes. Through thought experiments, students developed proposals for the adaptive reuse of threatened buildings, showcasing the potential for innovative solutions. The findings highlight the need to equip not only architects and planners, but also developers, investors, and policymakers with the knowledge and tools to prioritize building preservation. Early involvement of architects, beginning in Phase 0 (the pre-planning phase), and the reintroduction of demolition permits are identified as crucial strategies for aligning the built environment with sustainability objectives and safeguarding buildings for future generations.